Clinical and radiographic comparison by analyzed cone beam CT between one stage and two stage dental implants - Yildirm, Tuba Talo; Kaya, Filiz Acun; Yokus, Beran; Colak, Mehmet; Ozdemir, Eylem; Tekin, Gulucag Giray; Uysal, Ersin (University of Dicle, 2017)
The aim of this study is to evaluate the relationship between the periodontal clinical parameters and alveolar bone loss rate (ABLR) values in one and two stage dental implants using dental tomography A total of 40 dental implant was applied to patients, 20 a one-stage surgical procedure (group I) other 20 two-stage surgical procedure (group II), who had a single missing tooth in the lower jawbone. All clinical measurements were recorded at before loading (T0), after loading at the 3 rd month (T1) and after loading at the 6 th month (T2). Alveolar bone loss rate (ABLR) values were evaluated at T0 and T3 using dental tomography because of minimal artifacts and distortions. In our study, PPD was found to be significantly high in group I than group II at T1 and T2. There was a significant relation between the mPI and ABLR at T2 in Group I, also KSTI and ABLR at T0 in Group II. The data of this study confirms that; one stage surgery procedure PPD is high than two stage surgery procedure. Larger scale studies, particularly in peri-implantitis cases, may shed more light on this subject.
Keywords: Dental implant; Dental tomography; One stage surgery; Two stage surgery